Blood Cell Concentration Oscillations in Healthy and Tumors Affected Organisms - Berezin AA; Shmid AV (Annals of Circulation - Peertechz Publications, 2018)
Daily oscillations in the concentrations of segmented neutrophils and lymphocytes in mice and humans (both healthy and affected by acute and genetically inherited leukemia, solid tumors and some infl ammatory diseases) were studied. The analysis showed the breakage of phase synchronization of daily oscillations only in all cases of tumor diseases whereas is in cases of infl ammatory diseases the phase remained synchronized.